Automated software system to promote anticoagulation and reduce stroke risk: Cluster-randomized controlled trial - Holt, T; Dalton, A; Marshall, T; Fay, M; Qureshi, N; Kirkpatrick, S; Hislop, J; Lasserson, D; Kearley, K; Mollison, J; Yu, L; Hobbs, F; et al. (American Heart Association, 2017)
BACKGROUND AND PURPOSE: Oral anticoagulants (OAC) substantially reduce risk of stroke in atrial fibrillation, but uptake is suboptimal. Electronic health records enable automated identification of people at risk but not receiving treatment. We investigated the effectiveness of a software tool (AURAS-AF [Automated Risk Assessment for Stroke in Atrial Fibrillation]) designed to identify such individuals during routine care through a cluster-randomized trial. METHODS: Screen reminders appeared each time the electronic health records of an eligible patient was accessed until a decision had been taken over OAC treatment. Where OAC was not started, clinicians were prompted to indicate a reason. Control practices continued usual care. The primary outcome was the proportion of eligible individuals receiving OAC at 6 months. Secondary outcomes included rates of cardiovascular events and reports of adverse effects of the software on clinical decision-making. RESULTS: Forty-seven practices were randomized. The mean proportion-prescribed OAC at 6 months was 66.3% (SD=9.3) in the intervention arm and 63.9% (9.5) in the control arm (adjusted difference 1.21% [95% confidence interval -0.72 to 3.13]). Incidence of recorded transient ischemic attack was higher in the intervention practices (median 10.0 versus 2.3 per 1000 patients with atrial fibrillation; P=0.027), but at 12 months, we found a lower incidence of both all cause stroke (P=0.06) and hemorrhage (P=0.054). No adverse effects of the software were reported. CONCLUSIONS: No significant change in OAC prescribing occurred. A greater rate of diagnosis of transient ischemic attack (possibly because of improved detection or overdiagnosis) was associated with a reduction (of borderline significance) in stroke and hemorrhage over 12 months. CLINICAL TRIAL REGISTRATION: URL: http://www.isrctn.com. Unique Identifier: ISRCTN55722437.